Efficacy of Sacral Erector Spinae Plane Block for Postoperative Pain Management in Hemorrhoid and Pilonidal Sinus Surgeries: A Prospective Randomized Controlled Study - Koç, Alparslan; Akyol, Fethi; Huyut, Mehmet Tahir; Memis, Ufuk; Gazi, Mustafa; Sayar, Ali Caner; Somunkıran, Mustafa (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
This study was conducted to evaluate the efficacy of the sacral erector spinae plane block (ESPB) in postoperative pain management. We aimed to demonstrate the effectiveness of sacral ESPB implemented alongside analgesic treatment in patients undergoing hemorrhoid and pilonidal sinus (PS) surgeries.The study design involves a prospective randomized controlled. Sixty-eight patients were randomly divided into a sacral ESPB group and a control group. Following surgery, the ESPB group received an ultrasound-guided injection of a local anesthetic. Both groups received standardized pain management protocols. Pain scores were recorded using the numeric rating scale at 30 minutes, 2 hours, 8 hours, and 24 hours after surgery. Additionally, tramadol consumption and hospital length of stay were also recorded.Patients in the sacral ESPB group had significantly lower pain scores at 8 and 24 hours compared with the control group. They also consumed less tramadol on average. There were no significant differences in pain scores or tramadol use between patients who underwent hemorrhoid surgery and those who underwent PS surgery.Sacral ESPB effectively managed postoperative pain and reduced analgesic consumption in hemorrhoid and PS surgeries. The results of this study suggest that incorporating sacral ESPB into multimodal analgesic protocols for anorectal surgery may be clinically beneficial.
Keywords: analgesic techniques; postoperative recovery; pain management; erector spinae block; surgical outcomes; anorectal surgery